Fire Detection Alarm and Electric Circuit Breaker based on SIM800L Arduino - Kadek Reda Setiawan Suda; Abdillah Aziz Muntashir; I Komang Gede Suka Wijana; Muhdalifah Muhtar; Ida Bagus Putu Widja; I Wayan Nova Eka Ariana (Politeknik Pertanian Negeri Samarinda, 2026)
The danger of fire can have fatal consequences such as loss of property and even loss of life. Preventive action is necessary to avoid, prevent and minimize the occurrence of fire disasters. This research aims to design and build a smoke and fire detection system based on sensors, microcontrollers, which can be used to detect potential fire hazards in certain houses or buildings. The research method in designing this system refers to the prototyping model. The components used are MQ-02 sensors, KY-026 sensors, microcontrollers, alarm buzzers, and SMS notification senders and GSM calls using the SIM800L module. The results of the research are a fire detection alarm system and electricity circuit breaker, which functions to provide early warning of potential fires through buzzer alarms and SMS notifications and GSM calls. This system can be used to help detect and avoid potential fire hazards